2022
DOI: 10.1021/acsanm.2c01016
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabeled Human Protein-Functionalized Upconversion Nanoparticles for Multimodal Cancer Imaging

Abstract: Multimodal imaging removes the intrinsic limitations of individual modalities, while the multipurpose nanoagents reduce the toxicity associated with the use of multiple contrast agents. However, limited functionality, inefficient or incompatible targeting, and unknown biodistribution are significant drawbacks for such complicated nanodesigns. We report a biofriendly pentamodal imaging agent with the synergistic dual-targeting ability (passive and active) based on fluoromagnetic NaGdF4:Yb,Er upconverting nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…There are four general ways to fabricate a theranostic particle: (i) therapeutic agent can be encapsulated or conjugated onto imaging NPs such as SPION, UCNPs, quantum dots, etc. [ 67 , 68 , 69 ], (ii) CA can be tagged onto a therapeutic nanoparticle such as silver nanoparticles, etc. [ 70 ], (iii) both the CA and therapeutic agent can be encapsulated onto a biocompatible NPs such as polymeric NPs, nano-vesicles, MSN, etc., (iv) engineering of unique NPs with imaging and therapeutic potential is possible with PEGylation to improve biocompatibility.…”
Section: Applicationsmentioning
confidence: 99%
“…There are four general ways to fabricate a theranostic particle: (i) therapeutic agent can be encapsulated or conjugated onto imaging NPs such as SPION, UCNPs, quantum dots, etc. [ 67 , 68 , 69 ], (ii) CA can be tagged onto a therapeutic nanoparticle such as silver nanoparticles, etc. [ 70 ], (iii) both the CA and therapeutic agent can be encapsulated onto a biocompatible NPs such as polymeric NPs, nano-vesicles, MSN, etc., (iv) engineering of unique NPs with imaging and therapeutic potential is possible with PEGylation to improve biocompatibility.…”
Section: Applicationsmentioning
confidence: 99%
“…17 Presently, an in-depth investigation of the in vivo biodistribution of radiolabeled UC nanomaterials is of utmost importance for the development of potential multimodal imaging contrast agents and clinical transfer. Recently, Akhtar et al 18 reported the use of NaGdF 4 :Yb,Er upconversion nanoparticles (UCNPs) as contrast agents for multimodal cancer imaging. The radiolabel, 99m Tc, was employed for SPECT imaging, and Yb presented the potential for CT imaging.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to the emergence of many innovative strategies for nanotheranostics and new approaches for personalized medicine. Owing to their distinctive optical properties, such as the absence of blinking, low excitation rates, and high emission signal-to-noise ratio, rare-earth doped upconverting nanoparticles (UCNPs) have proven to be promising candidates for the detection, visualization, and treatment of various diseases. Moreover, UCNPs after additional doping of the UCNPs matrix with Lu 3+ , Ho 3+ , Sm 3+ , or Gd 3+ ions could be used as multimodal contrast agents for computed tomography, , magnetic resonance imaging, , and single-photon emission computerized tomography . Recently, it was demonstrated that upconverting nanoparticles are also promising as remote thermal nanoprobes, particularly for monitoring treatment progress or inducing tissue inflammation, where direct temperature measurement is critical .…”
Section: Introductionmentioning
confidence: 99%